Mid‐term Outcomes of the Helex Septal Occluder for Percutaneous Closure of Secundum Atrial Septal Defects. (1st March 2013) - Correa, Rafael; Zahn, Evan; Khan, Danyal
Abstract Background The HELEX Septal Occluder (HSO) was approved by the Food and Drug Administration for closure of secundum atrial septal defects (ASD) in 2006. However, little mid‐term follow‐up information is available. The object of this study was to examine mid‐term outcomes after HSO implantation Methods A retrospective chart review was performed on the first 74 patients who underwent ASD closure with the HSO between 4/00–10/04. Only patients who left the catheterization laboratory after successful implantation and had a minimum follow‐up of 5 years were selected for analysis. Results Thirty‐three patients met entry criteria. At implantation the mean age was 10.9 years and the median ASD size was 15.1 mm. At a median follow‐up of 88 months, 26 patients had complete ASD closure, 6 had trivial left‐right shunts, and 1 had a significant residual shunt having a reintervention. Fluoroscopy, performed in 27 patients revealed a frame fracture in 3 patients (9%), all of whom were asymptomatic and had effective ASD closure. All 3 devices were 30 mm or 35 mm HSO and were left in place. One patient developed first‐degree heart block and remained asymptomatic with no progression. There were no instances of late device embolization, cardiac perforation, erosion, or death. Conclusions Following successful implantation, HSO results in effective closure of secundum ASD in mid‐term follow‐up. Late complications appear to be rare with the exception of frame fracture, which in this series did not result in clinical sequelae.